Economic impact of hotels and similar establishments in Veszprém District - Alishan Karimov; Petra Gyurácz-Németh; Dirk-Jan F. Kamann (REGION, 2023)
This study measures the economic impact of hotels and similar establishments on the overall economy of the Hungarian Veszprém District. It is considered to be an individual part of the total hospitality sector. The Local Multiplier is utilized in the study from three perspectives: direct, indirect and induced effects. Both secondary public data as well as primary data sources, merely questionnaires, were used to collect data. The resulting score for the induced impact (LM3) is 1.96, meaning that for every forint brought into the economy of the district of Veszprem by the hotels and similar establishments, another extra forint is generated. The study also finds that revenues of the Veszprem district as share of the national figures have shrunk significantly and development has stagnated in absolute terms over the past four years.
Keywords: 330; hotel; local multiplier; Veszprém; hospitality industry